2002
DOI: 10.1016/s0960-9822(02)00713-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ins(3,4,5,6)P4 Signaling by a Reversible Kinase/Phosphatase

Abstract: Regulation of Cl(-) channel conductance by Ins(3,4,5,6)P(4) provides receptor-dependent control over salt and fluid secretion, cell volume homeostasis, and electrical excitability of neurones and smooth muscle. Ignorance of how Ins(3,4,5,6)P(4) is synthesized has long hindered our understanding of this signaling pathway. We now show Ins(3,4,5,6)P(4) synthesis by Ins(1,3,4,5,6)P(5) 1-phosphatase activity by an enzyme previously characterized as an Ins(3,4,5,6)P(4) 1-kinase. Rationalization of these phenomena wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 23 publications
(1 reference statement)
2
80
2
Order By: Relevance
“…1A). This is a biologically significant phenomenon that enables Ins(1,3,4)P 3 to regulate Ins(3,4,5,6)P 4 accumulation in vivo (8), but it has not previously been rationalized at a molecular level. We now show that Ins(1,3,4)P 3 considerably reduced the quantity of [ Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). This is a biologically significant phenomenon that enables Ins(1,3,4)P 3 to regulate Ins(3,4,5,6)P 4 accumulation in vivo (8), but it has not previously been rationalized at a molecular level. We now show that Ins(1,3,4)P 3 considerably reduced the quantity of [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). These reactions have been demonstrated to be reversible: ITPK1 can also dephosphorylate Ins(1,3,4,5,6)P 5 back to Ins(3,4,5,6)P 4 (8). An especially puzzling aspect of this phenomenon is that dephosphorylation of Ins(1,3,4,5,6)P 5 by human ITPK1 is stimulated, rather than competitively inhibited, by one of its alternate substrates, Ins(1,3,4)P 3 (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We now report that the three other GmItpk isoforms also show this activity: type 1 = 403 ± 4, type 3 = 487 ± 47, type 4 = 88 ± 16 (lmol/ mg protein/min), albeit at rates 6-to 33-fold lower than that of the type 2 enzyme. Substrate cycling between Ins(3,4,5,6)P 4 and Ins(1,3,4,5,6)P 5 may serve a signaling role in plants, in which Ins(3,4,5,6)P 4 has been shown to regulate Cl À channel conductance [15], similar to the role of Ins(3,4,5,6)P 4 in animal cells [22].…”
Section: Synthesis Of Ins(3456)p 4 By Soybean Itpksmentioning
confidence: 97%
“…As well as exhibiting Ins(3,4,5,6)P 4 1-kinase activity, mammalian Itpk1 has been shown to dephosphorylate Ins(1,3,4,5,6)P 5 to Ins(3,4,5,6)P 4 [16,22]. We recently demonstrated that GmItpk2 can also dephosphorylate Ins(1,3,4,5,6)P 5 to Ins(3,4,5,6)P 4 (2932 ± 50 lmol/mg protein/min) [16].…”
Section: Synthesis Of Ins(3456)p 4 By Soybean Itpksmentioning
confidence: 99%